Agro-industrial enterprises’ resource support transformation in the course of system integration - D. V. Serdobintsev; E. A. Aleshina (E-Management, 2022)
Currently, the Russian economy is undergoing active processes of digital transformation and system integration in all areas of production and economic activity. At the same time, the agro-industrial complex and agriculture lag behind the leading industries in terms of the level of digitalisation. This opens up large-scale prospects for the implementation of information technology projects, but also dictates the need to introduce additional measures to accelerate the development and implementation of digital technologies. The growing popularity of system integration is explained by a number of advantages: reducing the time for information exchange, decision-making and goods circulation, eliminating duplication of functions and the overall economic effect for each of the participants due to a wider and more comprehensive integration of computer systems. To support such initiatives, the study proposes a mechanism for the system integration of the resource subsystem of agricultural, processing and marketing enterprises in the region using a theoretical and methodological basis. Achieving the highest level of system integration is expected through the integration of information systems on a platform framework, as well as the addition of digital services of financial operators with the connection of economic entities of the agro-industrial complex. The developed mechanism reflects the algorithm of strategically significant events with a target orientation towards expanding the scale of system integration of enterprises in the agro-industrial complex. Its implementation will provide an opportunity for global planning in industries and provision of recommendations to market participants, including those based on artificial intelligence technologies.